2012
DOI: 10.1177/1087057111421623
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alerts for Predicting Clastogenic Activity of Pro-oxidant Flavonoid Compounds: Quantitative Structure–Activity Relationship Study

Abstract: Flavonoids have been reported to exert multiple biological effects that include acting as pro-oxidants at very high doses. The authors determined a structural alert to identify the clastogenic activity of a series of flavonoids with pro-oxidant activity. The methodology was based on a quantitative structure-activity relationship (QSAR) study. Specifically, the authors developed a virtual screening method for a clastogenic model using the topological substructural molecular design (TOPS-MODE) approach. It repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…We think it is interesting to predict, from the standpoint of polyphenolic structure-activity, the DNA damage leading to pro-oxidant substances (Yordi et al, 2011). Aruoma (2003) described that oxidative modifications to DNA are very important.…”
Section: New Challenges In Pro-oxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…We think it is interesting to predict, from the standpoint of polyphenolic structure-activity, the DNA damage leading to pro-oxidant substances (Yordi et al, 2011). Aruoma (2003) described that oxidative modifications to DNA are very important.…”
Section: New Challenges In Pro-oxidant Activitymentioning
confidence: 99%
“…We believe that these methods can be useful for predicting a specific activity of new polyphenolic compounds and/or synthezinging polyphenols with desired properties (Yordi et al, 2011).…”
Section: Qsar Studies and Antioxidant/pro-oxidant Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of phenolic substances with clastogenic activity. It has also been predicted by in silico studies that some substances reported to have pro-oxidant activity can be clastogenic [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to predict the clastogenic activity of phenolic compounds with reported pro-oxidant activity, QSAR methods have been employed [13,14] and they have been interpreted, in structural terms, structure-activity relationships. This has allowed the identification of structural alerts associated with clastogenic activity using the TOPSMODE approach.…”
Section: Introductionmentioning
confidence: 99%